The Role of the Principal in Rohis Da'wah Activities in Schools - Maryance Maryance; Wira Alvio; Bambang Irawan; Silvia Assoburu; Hera Zulaiha (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
The concept of Rohis Da'wah is a common practice in Islamic schools, which has been widely used to promote religious tolerance and tolerance among Muslim students. This study aims to comprehensively analyze the effectiveness of principals' strategies in promoting religious tolerance in schools. The research findings would highlight the principal's effectiveness in fostering religious tolerance and shed light on the broader impact of such efforts on creating a more harmonious and accepting society. The research shows that students exposed to different religious beliefs gain a broader understanding of the world and develop stronger critical thinking skills. Furthermore, the findings of this research would provide valuable insights into the long-term effects of such initiatives and their significance for the students' future lives and society as a whole.